The preterm gut microbiota and administration routes of different probiotics: a randomized controlled trial - Rahkola Ella-Noora; Rautava Samuli; Hiltunen Henni; Ross Chandler; Lahti Leo; Isolauri Erika (SPRINGERNATURE, 2025)
Background
Preterm children with their aberrant gut microbiota and susceptibility to infections and inflammation constitute a considerable target group for probiotic therapy to generate the age-appropriate healthy microbiota.
Methods
68 preterm neonates were randomized into five intervention groups: Beginning from the median age of 3 days, 13 children received Lactobacillus rhamnosus GG (LGG) directly orally, and 17 via the lactating mother. 14 children received LGG with Bifidobacterium lactis Bb-12 (Bb12) orally, and 10 via the lactating mother. 14 children received placebo. The children's faecal microbiota was assessed at the age of 7 days by 16S rRNA gene sequencing.
Results
The gut microbiota compositions of the children directly receiving the probiotic combination (LGG + Bb12) were significantly different from those of the children receiving the other intervention modes or placebo (p = 0.0012; PERMANOVA), the distinction being due to an increase in the relative abundance of Bifidobacterium animalis (P < 0.00010; ANCOM-BC), and the order Lactobacillales (P = 0.020; ANCOM-BC).
Conclusion
The connection between aberrant primary gut microbiota and a heightened risk of infectious and non-communicable diseases invites effective microbiota modulation. We show that the direct, early, and brief probiotic intervention of LGG + Bb12 10(9) CFU each, is sufficient to modulate the gut microbiota of the preterm neonate.
Impact
Preterm children have a higher risk of several health problems partly due to their aberrant gut microbiota.
More research is needed to find a safe probiotic intervention to modify the gut microbiota of preterm children. The maternal administration route via breast milk might be safer for the newborn.
In our study, the early and direct administration of the probiotic combination Lactobacillus rhamnosus GG with Bifidobacterium lactis Bb-12 increased the proportion of bifidobacteria in the preterm children's gut at the age of 7 days, but the maternal administration route was not as effective.